Produção de lipase por Candida viswanathii: otimização das condições de cultivo, purificação em sistema aquoso bifásico e propriedades bioquímicas - Teixeira, Mayra Ferreira Netto (Universidade Federal do Tocantins, 2017)
Lipases (EC 3.1.1.3) hydrolyze ester bonds of triacylglycerols at a water-oil interface. By they have several industrial applications, they are the enzymes most used in organic synthesis and more than 20% of biotransformations are performed with lipases. The objectives of this work were to evaluate the nutritional conditions of culture media (plant and animal oils, nitrogen and carbon) to improve the production of lipase by Candida viswanathii in addition to purifying the enzyme in a biphasic aqueous system and to realize the partial characterization of lipase. Among the culture media analyzed, the Vogel medium provided the highest lipase production after 36 hours of culture (11,73 U/mL). After analyzing the lipid and non-lipid carbon sources and nitrogen sources, an experimental design of blends was applied to analyze the effect of glycerol, lactose and sorbitol on lipase production. The results showed that the highest production of lipase (20,41 U/mL) was observed with 0.5% lactose (w/v) and 0.5% (w/v) sorbitol, with an increase of 74% of enzyme production. In this study it was observed that lactose and sorbitol were used as adjuncts for the production of lipase. The lipase produced under the above conditions was purified in a aqueous two-phase systems (ATPS) consisting of polyethylene glycol (PEG) and potassium phosphate. The highest partition coefficient (1,34) was found in the PEG 4000/phosphate assay at temperature of 40 °C and pH 7,0, as well as the highest activity balance (50,73%). In the partial characterization, the lipase was not influenced by the temperature range of 20 - 60 °C and obtained maximum activity at pH 8,1. The enzyme also showed high stability in organic solvents such as methanol and ethanol, and these properties are considered important for applications in biotechnological processes.